2013
DOI: 10.1016/j.watres.2012.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydraulic regimes on bacterial community structure and composition in an experimental drinking water distribution system

Abstract: Influence of hydraulic regimes on bacterial community structure and composition in an experimental drinking water distribution system. Water Research, 47 (2). 503 -516. ISSN 0043-1354 https://doi.org/10.1016/j.watres.2012.09.053 eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy sole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
185
5
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(204 citation statements)
references
References 61 publications
10
185
5
4
Order By: Relevance
“…Douterelo et al (2013) examined biofilms from drinking water distribution systems and found that the hydraulic regime influenced the bacterial composition and community structure. They also observed that flushing (sudden flow of fluid at high shear stresses inside the system) did not succeed in total biofilm removal but altered the biofilm microbial community.…”
Section: Introductionmentioning
confidence: 99%
“…Douterelo et al (2013) examined biofilms from drinking water distribution systems and found that the hydraulic regime influenced the bacterial composition and community structure. They also observed that flushing (sudden flow of fluid at high shear stresses inside the system) did not succeed in total biofilm removal but altered the biofilm microbial community.…”
Section: Introductionmentioning
confidence: 99%
“…Las bacterias fecales constituyen el principal indicador de riesgo patogénico dentro de los estándares microbiológicos para calidad de agua en la gran mayoría de los países (Sammon et al, 2010;Boubetra et al, 2011). Sin embargo, debido a que la presencia de Pseudomonas en el agua potable es un hecho bastante común (Nawrocki et al, 2010;Douterelo et al, 2013), muy recientemente se han sugerido como buenos indicadores de riesgo humano (Douterelo et al, 2016); siendo, además, una actualidad bien real que los nuevos enfoques y avances en procedimientos metodológicos han logrado evidenciar la proliferación de microorganismos, estructurados en comunidades bacterianas y fúngicas, cuya presencia han deteriorado la seguridad del vital líquido tanto en sus reservorios como en las redes de distribución que surten a los usuarios (Douterelo et al, 2016;Oliveira et al, 2016;Stauber et al, 2016).…”
Section: Resultados Y Discusiónunclassified
“…Más recientemente Douterelo et al (2016), reportaron que las fuentes de agua potable constituyen el "semillero" de los microorganismos formadores de biopelículas por sus capacidades de incrementar resistencia a la desinfección (Soniago et al, 2011;Pereira et al, 2013). De esta manera, muchos patógenos logran sobrevivir durante los tratamientos de desinfección de los reservorios de agua desde donde, dependiendo de las condiciones hidráulicas establecidas para el caudal, viajan a través de los sistemas de acueducto y gran parte de ellos pueden llegar hasta los usuarios en niveles que son directamente proporcionales a la velocidad del flujo (Douterelo et al, 2013;Holinger et al, 2014). En tal sentido, se podría indicar que mientras más rápido son transportados los distintos microorganismos dentro de las tuberías de suministro, se acorta su tiempo de estadía dentro de las mismas y, en consecuencia, también su posibilidad de formar biopelículas.…”
Section: Resultados Y Discusiónunclassified
“…Polyethylene pipe was selected as it is a prevalent and representative current material used in distribution systems world-wide. In order to provide representative water quality the facility is fitted with a trickle feed (and drain) from the local water distribution system [10].…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Most of biofilm research in DWDSs is based on studying the influence of the hydraulic conditions, the physical characteristics of the distribution system and the physico-chemical characteristics of the circulating water, among others, on biofilm development, besides from the interactions among microorganisms [19]. Although numerous studies have been carried out in relation to the influence that a number of characteristics of the DWDSs have on biofilm development [10,[20][21][22], in most cases, these characteristics are studied individually or in pairs, at most. Distribution systems are the major components of water utilities.…”
Section: Introductionmentioning
confidence: 99%